2001
DOI: 10.1073/pnas.020472198
|View full text |Cite
|
Sign up to set email alerts
|

An unusual isopentenyl diphosphate isomerase found in the mevalonate pathway gene cluster from Streptomyces sp. strain CL190

Abstract: A gene cluster encoding five enzymes of the mevalonate pathway had been cloned from Streptomyces sp. strain CL190. This gene cluster contained an additional ORF, orfD, encoding an unknown protein that was detected in some archaebacteria and some Grampositive bacteria including Staphylococcus aureus. The recombinant product of orfD was purified as a soluble protein and characterized. The molecular mass of the enzyme was estimated to be 37 kDa by SDS-polyacrylamide gel electrophoresis and 155 kDa by gel filtrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
137
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(144 citation statements)
references
References 16 publications
7
137
0
Order By: Relevance
“…Furthermore, they suggested that the enzyme-bound FMN intermediate that forms during the normal reaction is consistent with a neutral reduced dihydroflavin (4, Scheme 2). Although the steady-state kinetic parameters have been reported for a few IDI-2 enzymes (13,15,18,21,22,25), the nature of the rate limiting step(s) in the catalytic mechanism is unknown. In this paper, we report the investigation of the FMN intermediate formed during the catalysis of S. aureus IDI-2 using UV-vis and EPR spectroscopies.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, they suggested that the enzyme-bound FMN intermediate that forms during the normal reaction is consistent with a neutral reduced dihydroflavin (4, Scheme 2). Although the steady-state kinetic parameters have been reported for a few IDI-2 enzymes (13,15,18,21,22,25), the nature of the rate limiting step(s) in the catalytic mechanism is unknown. In this paper, we report the investigation of the FMN intermediate formed during the catalysis of S. aureus IDI-2 using UV-vis and EPR spectroscopies.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…The reactants were allowed to mix for variable lengths of time (from 3 ms to 1 s) prior to quenching with a solution of HCl/MeOH (25%). Each time point was acquired in duplicate, and the transfer of the 14 C radiolabel from IPP to DMAPP at each quenched time point was determined using a modified Satterwhite activity assay (13). Each quenched sample was immediately incubated at 37 °C for 10 min to allow conversion of the acid-labile DMAPP product into a mixture of extractable alcohols and methyl ethers.…”
Section: Rapid Chemical Quench Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Type II IPP isomerase was first reported in 2001 (15). In contrast to the type I enzyme, type II isomerase requires flavin mononucleotide (FMN), a reducing agent, typically NADPH, and a divalent metal for activity.…”
mentioning
confidence: 99%